Assessment of Avermectins-Induced Toxicity in Animals - Muhammad Salman; Rao Zahid Abbas; Khalid Mehmood; Riaz Hussain; Sehar Shah; Mehwish Faheem; Tean Zaheer; Asghar Abbas; Bernardo Morales; Ina Aneva; José L. Martínez (Pharmaceuticals, 2022)
Macrocyclic lactones, particularly the avermectins, have completely revolutionized the approaches aimed at control of parasites. These avermectins are the most widely used anti-parasitic drugs in veterinary field with sales exceeding one billion US dollars annually. However, before clinical usage, their safety evaluation in the animals is a major critical factor that must be considered. Many studies have reported the negative effects of avermectins like ivermectin, abamectin, doramectin, and eprinomectin on the host animals. These harmful effects arise from avermectins targeting GABA and glutamate-gated chloride channels present both in the parasites and the host animals. In this review, various modes of avermectins action along with the negative effects on the host like nephrotoxicity, hepatotoxicity, neurotoxicity, reproductive toxicity, and endocrine disruption were discussed in detail. Furthermore, other important issues like ecotoxicity, drug resistance, and drug residues in milk associated with avermectins usage were also discussed, which need special attention.